BUSINESS MODEL BESORC - Škafar, Branko (Anali PAZU, 2022)
This paper presents a unique business model BESORC. Model name derives from the initials of these words exellence BUSINESS AND SOCIAL resposibility COMPANY. The model is a modified and tested in practice good results. The model contains elements of quality tools, and excellence, ethics, sustainable development, proper leadership, motivation, communication, innovation and constant change. Using the model enables organizations to successfully cope with the crisis and are in the long run efficient and effective.